Implementasi Google Workspace dalam Manajemen Pendidikan Islam di MTs Al Anwar Perak Jombang - Sutrisno, Sutrisno (Muróbbî: Jurnal Ilmu Pendidikan, 2025)
Technological advancements have compelled schools and educational institutions in Indonesia to adapt without compromising their cultural identity and values. Traditional Islamic education is based on face-to-face learning and direct interaction between teachers and students. However, with the development of technology, Islamic educational institutions have begun to adapt to modern approaches without neglecting religious values. This is important to ensure that the implementation of technology can support Islamic values in education, including ethics, discipline, and openness to the times. In boarding school-based schools such as MTs Al Anwar, the integration of Google Workspace offers benefits in terms of information management and distribution, as well as more structured learning activity management. This implementation aims to improve operational efficiency, accelerate communication, and create a more collaborative work culture, and is expected to increase administrative efficiency and collaboration among teachers, students, and school staff as a whole. This research aims to explore the implementation of Google Workspace in Islamic education management at MTs Al Anwar Perak Jombang, particularly in the aspects of administration and learning.